Presence of Metals in Farmland Edible Termites in Mazabuka District, Zambia - Kapaale, Meekness; Andika, Darius Otiato; Nkunika, Philip Obed Yobe (African Journal of Agricultural Research, 2021)
Edible termites have played an important role in the history of human nutrition due to their nutritional value. Despite their nutritional body content, it is known that during their termitarium construction, termites accumulate metals in their bodies. This study examined the heavy metal content in selected edible termites for food safety. The household survey was carried out in 8 camps of Magoye and Stateland farming blocks in Mazabuka district. The study was done to determine human activities in the farmlands. A structured questionnaire was used to collect data via one-on-one interview. A total of 362 respondents participated and their farmland activities included; mixed farming, agrochemical usage, transportation, milling, mining and termite harvesting. Composite samples of selected edible soldier termites and the nest soil were analysed for the presence of Cu, Co, Pb, Mn, Ni, Zn, Fe using atomic absorption spectrophotometer. Results in nest soil showed all analysed metals, with Mn having the highest mean 6.65±1.73 mg/L and sampled termites showed presence of all heavy metals except Ni and Co, with Fe having the highest mean value of 5.38±4.75 mg/L. ANOVA revealed a significant difference with P<0.05 in Co, Mn, Zn, Ni in nest soil and no significant difference in sampled termites. There was no significant Pearson correlation between heavy metals in soil and edible termites, suggesting an active regulation of metals by termites.
Keywords: Edible Insects; Entomophagy; Termitarium; Magoye; Zambia